Development of Zero Cross Correlation-Double Weight Code for Optical CDMA - Babekir Idriss, Elamin Idriss (2007)
Optical fibers are very attractive communication media if compared to the conventional guided media like twisted wire pairs and coaxial cables since they offer large bandwidth and low attenuation. Hence, by utilizing optical fibers as the media of communication links, more advantages can be obtained if compared to traditional media. The three major multiple access for optical networks are Time Division Multiple Accees (TDMA), Frequency Division Multiple Access (FDMA) and Code Division Multiple Access (CDMA). OCDMA has advantages over TDMA and FDMA because first of all it makes efficient use of communication media by allowing asynchronous access to each user. Second no scheduling is required in CDMA and new users can easily be added to the networks. The Optical Code Division Multiple Access (OCDMA) suffers from various types of noise but the dominant source of noise is Multiple Access Interference (MAl). Therefore, the cancellation or suppression of MAl is a big problem in OCDMA. Much OCDMA codes have been designed to reduce the MAl and to enhance the performance of the system. This thesis concentrates on how to reduce the MAl in OCDMA. In this thesis Zero Cross Correlation-Double Weight Code (ZCC-DW) is proposed based on Modified Double Weight Code (MDW) for OCDMA system to decrease the cross correlation value from one to zero hence the Multiple Access Interference (MAl) should be decrease and this will improve the system performance. After completion the code construction techniques a simulation is used to study the performance of ZCC-DW code. The performance is carried out to various data rate and various optical fiber lengths to calculate the Bit Error Rate (BER) which it used to evaluate the code performance. Lastly Comparisons are then made between Direct Detection (ZCC-DW code Detection) and Hybrid Detection (MDW code Detection). Direct Detection Technique offers better result than Hybrid Detection Technique.